Distinct roles of adipose triglyceride lipase and hormone-sensitive lipase in the catabolism of triacylglycerol estolides - Brejchova, Kristyna; Radner, Franz Peter Walter; Balas, Laurence; Paluchova, Veronika; Cajka, Tomas; Chodounska, Hana; Kudova, Eva; Schratter, Margarita; Schreiber, Renate; Durand, Thierry; Zechner, Rudolf; Kuda, Ondrej (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Branched esters of palmitic acid and hydroxy stearic acid are antiinflammatory and antidiabetic lipokines that belong to a family of fatty acid (FA) esters of hydroxy fatty acids (HFAs) called FAHFAs. FAHFAs themselves belong to oligomeric FA esters, known as estolides. Glycerol-bound FAHFAs in triacylglycerols (TAGs), named TAG estolides, serve as metabolite reservoir of FAHFAs mobilized by lipases upon demand. Here, we characterized the involvement of two major metabolic lipases, adipose triglyceride lipase (ATGL) and hormone-sensitive lipase (HSL), in TAG estolide and FAHFA degradation. We synthesized a library of 20 TAG estolide isomers with FAHFAs varying in branching position, chain length, saturation grade, and position on the glycerol backbone and developed an in silico mass spectra library of all predicted catabolic intermediates. We found that ATGL alone or coactivated by comparative gene identification-58 efficiently liberated FAHFAs from TAG estolides with a preference for more compact substrates where the estolide branching point is located near the glycerol ester bond. ATGL was further involved in transesterification and remodeling reactions leading to the formation of TAG estolides with alternative acyl compositions. HSL represented a much more potent estolide bond hydrolase for both TAG estolides and free FAHFAs. FAHFA and TAG estolide accumulation in white adipose tissue of mice lacking HSL argued for a functional role of HSL in estolide catabolism in vivo. Our data show that ATGL and HSL participate in the metabolism of estolides and TAG estolides in distinct manners and are likely to affect the lipokine function of FAHFAs.
Keywords: metabolismus; Stearic Acids; Mice, Knockout; HEK293 buňky; mastné kyseliny; sterolesterasa; tuková tkáň; FAHFA; Palmitic Acid; Sterol Esterase; HEK293 Cells; lipokine; ATGL; kyselina palmitová; lipasa; Fatty Acids; triglyceridy; bílá tuková tkáň; Adipose Tissue, White; myši knockoutované; lipolýza; Animals; lidé; Adipose Tissue; ženské pohlaví; Humans; zvířata; estery; Lipolysis; kyseliny stearové; myši; Esters; Metabolism; HSL; Lipase; Mice; Female; Triglycerides